2016
DOI: 10.5056/jnm15138
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Serotonin Receptor 3E Gene as a Functional Variant in the MicroRNA-510 Target Site with Diarrhea Predominant Irritable Bowel Syndrome in Chinese Women

Abstract: Background/AimsThe functional variant (rs56109847) in the 3′-untranslated regions (3′-UTR) of the serotonin receptor 3E (HTR3E) gene is associated with female diarrhea predominant irritable bowel syndrome (IBS-D) in British populations. However, the relationship of the polymorphism both to HTR3E expression in the intestine and to the occurrence of Chinese functional gastrointestinal disorders has yet to be examined. MethodsPolymerase chain reaction amplification and restriction fragment length polymorphism ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Therefore, we performed a meta-analysis to estimate the association between HTR3A and HTR3E polymorphisms and the risk for IBS-D. To the best of our knowledge, this is the first meta-analysis to explore the relationships between HTR3A and HTR3E gene polymorphisms and IBS-D susceptibility. Five case-control studies [ 11 14 , 26 ] with a total of 1,287 IBS-D patients and 1,418 healthy controls were included in our meta-analysis, which was giving a greater power to detect IBS-D risk associated with HTR3A and HTR3E gene polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we performed a meta-analysis to estimate the association between HTR3A and HTR3E polymorphisms and the risk for IBS-D. To the best of our knowledge, this is the first meta-analysis to explore the relationships between HTR3A and HTR3E gene polymorphisms and IBS-D susceptibility. Five case-control studies [ 11 14 , 26 ] with a total of 1,287 IBS-D patients and 1,418 healthy controls were included in our meta-analysis, which was giving a greater power to detect IBS-D risk associated with HTR3A and HTR3E gene polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic predisposition has been demonstrated in classical family/twin studies and epidemiological surveys, but unequivocal susceptibility genes have yet to be identified [ 2 , 10 ]. Recently, several genetic association studies identified the serotonin receptor type 3 (5-HT 3 ) subunit genes HTR3A and HTR3E polymorphisms as being significantly associated with IBS ( particularly IBS-D) [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, none of the miRNAs detected to be deregulated in IBS‐D in our study did overlap with any miRNAs that have previously been reported in IBS. This might be attributed to gut region‐ and/or serum‐specific differences and different etiopathology since all studies but one were from non–PI‐IBS cases 17‐26,28,29 . In line with the different structure and function of the proximal and distal gut, previously differential expression profiles of miRNAs in small versus large intestine have been described that might also contribute to discrepancies in study findings 40 .…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, microRNAs (miRNAs) serve as critical regulators in IBS‐D. For example, downregulation of miR‐510 can lead to IBS‐D . miR‐495, mapped in the 14q32.31 cluster, plays a crucial role not only in promoting the development of normal tissues but also regulating proliferation, apoptosis, metastasis, and chemosensitivity in cancer cells .…”
Section: Introductionmentioning
confidence: 99%